2008
DOI: 10.1007/s10856-008-3476-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of crosslinked hyaluronic acid hydrogels

Abstract: In order to improve the mechanical properties and control the degradation rate of hyaluronic acid (HA) an investigation of the structural and mechanical properties of the hydrogels crosslinked using divinyl sulfone (DVS), glutaraldehyde (GTA) and freeze-thawing, or autocrosslinking has been carried out. The thermal and mechanical properties of the gels were characterised by differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA) and compression tests. The solution degradation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 20 publications
11
73
0
6
Order By: Relevance
“…This difference could be attributed either to the different crosslinking degree [11] (in our case the molar ratio is 0.8), or to differences in level of hydration [11], as well as to the higher frequency of DMA measurements [40]. In Figure 5, it is shown that the recorded glass transition temperature decreases with water fraction starting from the sample of h w =0.06 until a critical water fraction located at about h w =0.31 and seems to stabilize for higher water fraction values at about T=-80 o C. The stabilization takes place in a water fraction region where water crystallization occurs during cooling (that is for h w ≥0.31, in the experimental range studied here).…”
Section: Dsc Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference could be attributed either to the different crosslinking degree [11] (in our case the molar ratio is 0.8), or to differences in level of hydration [11], as well as to the higher frequency of DMA measurements [40]. In Figure 5, it is shown that the recorded glass transition temperature decreases with water fraction starting from the sample of h w =0.06 until a critical water fraction located at about h w =0.31 and seems to stabilize for higher water fraction values at about T=-80 o C. The stabilization takes place in a water fraction region where water crystallization occurs during cooling (that is for h w ≥0.31, in the experimental range studied here).…”
Section: Dsc Measurementsmentioning
confidence: 99%
“…For these reasons it becomes clear that the study of the dynamics of water interacting with HA cross-linked materials is of great significance for biomedical applications. The physical but also the hydration properties of HA, in terms of different states of water (free, bound, loosely bound water or crystallized and uncrystallized water (UCW)) in the material, are frequently studied, among other experimental techniques, by differential scanning calorimetry (DSC) [9][10][11] and (FTIR) [12], while theoretical simulation studies contribute also to the field [13].…”
Section: ) Introductionmentioning
confidence: 99%
“…In order to improve the mechanical properties and control the degradability of HAbased hydrogels, HA can be chemically modified or physically crosslinked 15,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present work was to address the problems faced to produce the coating typologies just described, and to characterize their physicochemical state in the scaffold-coating construct. More specifically, answers were sought to questions such as: what is the adequate procedure to uniformly introduce an aqueous gel into a hydrophobic structure; what is the influence of solution concentration and of adsorption time on the type of coating obtained; how does the swelling capacity of the gel change as a consequence both of its typology (in the sense discussed above) and of its being constrained by the scaffold's elasticity; how does the system's porosity change with coating, how does porosity change when the gel swells inside the pores; and, finally, to what extent can the adsorbed HA be crosslinked in order to broaden its potential applications [12,[24][25][26][27][28], i.e., to prevent its rapid dissolution, to regulate its chemical stability, swelling, degradation and consequently its drugs release properties.…”
Section: Introductionmentioning
confidence: 99%